Effects of performance appraisal satisfaction on employees' satisfation of local and foreign banks in Singapore. - Chen, Michelle Huimei. (2008)
The objective of this comparative study is to explore whether a bank’s performance appraisals will affect employees’ satisfaction- job, supervisory and pay satisfaction in banks with different ownerships in Singapore, namely local and foreign banks. Other moderating and mediating effects will also be discussed.